2007
DOI: 10.1007/s11250-007-9010-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of semen collection frequency on seasonal variation in sexual behaviour, testosterone, testicular size and semen characteristics of tropical hair rams (Ovis aries)

Abstract: The purpose of this study was to examine the effect of day length on seminal characteristics, testicular size, sexual behaviour and testosterone (T4) concentration in pelibuey rams subjected to different semen collection frequencies. eighteen intact males were assigned randomly to one of two semen collection frequencies: in the high rate (HR) treatment, two ejaculations per week were obtained from each ram; one ejaculation every two weeks was collected under the low rate (LR) treatment. All animals were housed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
23
1
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 22 publications
(17 reference statements)
7
23
1
9
Order By: Relevance
“…Although differences were found in reaction time in the four breeds, the overall mean of 37.62 ± 4.89 seconds is within the reported range of 20 to 59 seconds in several sheep breeds , Kheradmand and Babaei 2006, Aguirre et al 2007 and is shorter than the average mentioned for mature hair rams (Chi et al 2009), young hair rams (Godfrey et al 1998, Lezama et al 2003, yearling Targhee rams (Price et al 1991) and for local wool breeds (Pimentel et al 2005). In relation to second and third mating, the overall mean of 136.43 ± 9.13 and 180.95 ± 11.46 seconds, respectively, is similar with the results of Chi et al (2009), but is lower than results reported in yearling Katahdin rams (Lezama et al 2003) and for local wool breeds (Pimentel et al 2005).…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Although differences were found in reaction time in the four breeds, the overall mean of 37.62 ± 4.89 seconds is within the reported range of 20 to 59 seconds in several sheep breeds , Kheradmand and Babaei 2006, Aguirre et al 2007 and is shorter than the average mentioned for mature hair rams (Chi et al 2009), young hair rams (Godfrey et al 1998, Lezama et al 2003, yearling Targhee rams (Price et al 1991) and for local wool breeds (Pimentel et al 2005). In relation to second and third mating, the overall mean of 136.43 ± 9.13 and 180.95 ± 11.46 seconds, respectively, is similar with the results of Chi et al (2009), but is lower than results reported in yearling Katahdin rams (Lezama et al 2003) and for local wool breeds (Pimentel et al 2005).…”
Section: Discussionsupporting
confidence: 53%
“…Time from the introduction of the ram and his first mating (reaction time) and latency (refractory period) between the first and second and between the second and third mating were recorded. At no time rams were allowed to copulate the exposed ewes, first due to health reasons and secondly because studies such as Aguirre et al (2007) and Cárdenas-Gallegos et al (2012), show that this method of assessment does not affect sexual behaviour of rams. It was considered as mating when rams mounted, penetrated and ejaculated into an artificial vagina.…”
Section: Ram Evaluationsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, hair sheep, a breed originated in the tropics, have been reported to be almost or completely aseasonal (Rosa and Bryant 2002, Aguirre et al 2007, Arroyo et al 2007, and no comparisons have been mande with wooled breeds regarding their mating activity.…”
Section: Introductionmentioning
confidence: 99%